Green Reputation in Mediating Implementation of Sustainable Development Goals (SDGs) On Company Financial Performance - Bisri, Hasan; Rahayu, Susilowati; Safii, Abdul Azis (Magister Akuntansi Universitas Pancasila, 2025)
This study aims to examine the mediating role of green reputation in the relationship between the implementation of Sustainable Development Goals (SDGs) and corporate financial performance. Research data processing using SEM-PLS Analysis. Data sourced from financial reports and sustainability reports published by the company, and ESG score data released by the IDX in collaboration with Morningstar Sustainalytics.The research findings found that although the implementation of SDGs does not have a direct impact on financial performance, there is a significant influence of the implementation of SDGs on green reputation, and green reputation has a significant influence on the company's financial performance, so that green reputation becomes a mediator between the implementation of SDGs on the company's financial performance. The theoretical implications of this study support signaling theory, where green reputation acts as a positive signal to stakeholders regarding a company's commitment to sustainability. In terms of policy, these results encourage companies to not only adopt SDGs, but also proactively build and strengthen their green reputation to maximize the positive impact on the company's financial performance. The novelty of this research lies in the use of the green reputation variable as a mediator with measurements using the ESG-Sutainalytics score.